EXPANDING THE SCOPE OF LAND ACQUISITION IN THE JOB CREATION LAW: BETWEEN INVESTMENT ACCELERATION AND LAND RIGHTS PROTECTION - Irsia Khairina, Ghassani (Suloh: Jurnal Fakultas Hukum Universitas Malikussaleh, 2026)
The amendment of the land acquisition legal regime through Law Number 6 of 2023 concerning Job Creation has brought fundamental implications to the concept of "Public Interest." This study aims to analyze the shift in the meaning of public interest, which was originally restricted to basic service infrastructure, to now include the development of strategic economic zones. The research method used is normative legal research with a statute approach and a conceptual approach. Legal materials were analyzed qualitatively to examine the expansion of land acquisition objects in Article 10 of Law No. 2 of 2012 jo. Job Creation Law. The results show that the redefinition of public interest has radically expanded to include exclusive commercial areas, such as Industrial Zones, Special Economic Zones (SEZ), and Tourism. This expansion marks a paradigm shift from a public service orientation (state-oriented) to a market orientation (market-oriented). This has resulted in a distortion of the state's power of eminent domain, where state instruments are utilized to facilitate asset accumulation for business entities (State-Owned Enterprises/Private). The juridical implication is the reduction of protection for land rights holders due to the elimination of voluntary agreement mechanisms (Business to Business) in commercial projects, as well as the increasing potential for agrarian conflicts due to the neglect of the social function of land. Keywords: Public Interest; Land Acquisition; Job Creation Law.